Analisis Pengaruh Indeks Pembangunan Manusia dan Pengangguran Terhadap Tingkat Kemiskinan di Sumatera Utara Menggunakan Metode Regresi Linear Berganda - Indah Febriani Sagala; Achmad Fajri Romadhoni; Annisya Mardiana; Ayu Widyasari; Demak Rotua Simamora; Dilla Nurfadiah; Ega Ananda Br Sembiring; Irvina Abelia Harahap; M.E Ernawati Siregar; M.Fajar Alif; Nagita Adella; Reski Augustian S; Richard Fernando Sihotang (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Poverty is a serious problem in Indonesia, including in North Sumatra. Various factors include the human development index (HDI) and unemployment rate. This research aims to analyze the influence of the Human Development Index (HDI) and unemployment on the poverty rate in North Sumatra using the method multiple linear regression to analyze secondary data obtained from the Central Statistics Agency (BPS) of North Sumatra. The variables used in this research are the HDI and unemployment, while the dependent variable is the poverty level. The results of the research show that the HDI and the unemployment rate have a significant influence on the poverty level. These findings show that to reduce poverty in North Sumatra, efforts are needed to increase the HDI through improving the quality of education, health and living standards of the community by increasing the HDI which provides efforts to prevent poverty from occurring.